Whom to Believe? Understanding and Modeling Brain Activity in Source Credibility Evaluation - Kawiak, Andrzej; Wojcik, Grzegorz M.; Schneider, Piotr; Kwasniewicz, Lukasz; Wierzbicki, Adam (Frontiers in Neuroinformatics, 2020)
Understanding how humans evaluate credibility is an important scientific question in the era of fake news. Source credibility is among the most important aspects of credibility evaluations. One of the most direct ways to understand source credibility is to use measurements of brain activity of humans performing credibility evaluations. Nevertheless, source credibility has never been investigated using such a method before. This article reports the results of an experiment during which we have measured brain activity during source credibility evaluation, using EEG. The experiment allowed for identification of brain areas that were active when a participant made positive or negative source credibility evaluations. Based on experimental data, we modelled and predicted human source credibility evaluations using EEG brain activity measurements with F1 score exceeding 0.7 (using 10-fold cross-validation).